Spheroidized carbonaceous negative electrode active material, method for producing the same, and negative electrode and lithium secondary battery containing the same

By mixing flaky graphite with asphalt and spheroidizing, and performing multi-step processing, a spheroidized carbonaceous negative electrode active material with reduced internal pores and improved spheroidism was prepared, which solved the density of negative electrode active material of lithium secondary battery The problems of low, poor expansion characteristics and poor high-temperature storage characteristics achieve better electrode performance.

CN114514638BActive Publication Date: 2025-02-18LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080066300.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-04
Filing Date
2020-09-29
Publication Date
2025-02-18
Estimated Expiration
2040-09-29

AI Technical Summary

Technical Problem

The negative electrode active materials of existing lithium secondary batteries produce a large number of internal pores during spheroidization, resulting in low density, poor expansion characteristics and poor high-temperature storage characteristics.

Method used

The spheroidized carbonaceous negative electrode active material is prepared by mixing flake graphite with solid asphalt and liquid asphalt and spheroidized, and the spheroidized carbonaceous negative electrode active material is reduced by calcining, carbon coating, heat treatment and disintegration steps.

Benefits of technology

The internal pore reduction and spherical improvement of the spherical active material after spherification are achieved, the internal stress and expansion characteristics of the electrode are reduced, and the capacity retention rate of high-temperature storage is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114514638B_ABST
    Figure CN114514638B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a spheroidized carbonaceous negative electrode active material, which comprises the following steps: mixing flaky graphite, solid asphalt and liquid asphalt, and spheroidizing the obtained mixture to prepare spheroidized granulated particles; calcining the spheroidized granulated particles; carbon coating the calcined spheroidized granulated particles; heat treating the carbon-coated spheroidized granulated particles; and disintegrating the heat-treated product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a spheroidized carbonaceous negative electrode active material, a preparation method thereof, a negative electrode and a lithium secondary battery comprising the same. More particularly, the present invention relates to a spheroidized carbonaceous negative electrode active material having reduced internal pores and improved sphericity, a preparation method thereof, a negative electrode and a lithium secondary battery comprising the same.

[0002] This application claims priority to Korean Patent Application No. 10-2019-0123398 filed in Korea on October 4, 2019, the disclosure of which is incorporated herein by reference. Background Art

[0003] As the technology of mobile devices develops and the demand increases, the demand for secondary batteries as energy sources for these mobile devices is also increasing. Among these secondary batteries, lithium secondary batteries with high energy density and operating voltage, long cycle life and low discharge rate have been commercialized and widely used.

[0004] The lithium secondary battery has the following structure, which includes: a battery assembly, the electrode assembly having a positive electrode and a negative electrode each containing an active material coated on an electrode current collector, and a porous separator interposed between the two electrodes; and an electrolyte containing a lithium salt injected into the electrode assembly. The electrode is obtained by applying a slurry containing an active material, a binder and a conductive material dispersed in a solvent to a current collector, followed by drying and rolling.

[0005] To date, lithium metal has been used as the negative electrode of secondary batteries. However, because lithium metal is known to cause short circuits in batteries due to lithium dendrite formation, leading to the risk of explosion, it has been replaced by carbonaceous compounds that can reversibly intercalate / deintercalate lithium ions while maintaining structural and electrical properties.

[0006] This carbonaceous compound has a significantly low discharge potential of about -3 V based on the standard hydrogen electrode potential, and exhibits excellent electrode cycle life due to significantly reversible charge / discharge behavior derived from the uniaxial orientability of the graphene layer. In addition, after lithium ion insertion, the carbonaceous compound exhibits a relatively low charge / discharge rate relative to Li / Li + The electrode potential is 0 V, which is substantially similar to the electrode potential of pure lithium metal. Therefore, when lithium metal is combined with an oxide-based positive electrode to form a battery, higher energy can be advantageously obtained.

[0007] As the carbonaceous compound, various types of carbonaceous materials including artificial graphite, natural graphite, and hard carbon have been used. Among the carbonaceous compounds, graphite is currently the most widely used.

[0008] Among various types of graphite, natural graphite is used after it is converted into graphite with a smooth surface shape through a post-processing process such as a spheroidization process to reduce irreversible reactions and improve the processing properties of the electrode. In addition, when natural graphite is surface-coated by heat treatment of low-crystalline carbon such as asphalt, the end face of the graphite can be prevented from being directly exposed, damage caused by the electrolyte can be prevented, and irreversible reactions can be reduced. Negative electrode material manufacturers use the following method: a negative electrode active material is prepared by coating spherical natural graphite with low-crystalline carbon.

[0009] However, the negative electrode active material obtained by the above method is a negative electrode active material prepared by spheroidizing natural graphite having a flaky particle shape, and the spheroidized graphite particles contain a large number of voids therein. Such voids reduce the density of the negative electrode active material, thereby making it difficult to manufacture a high-density negative electrode plate. In addition, because the low-crystalline carbon coating film is broken during the process of densifying the negative electrode active material on the collector, the graphite end face is exposed, causing problems of damage and irreversible reaction caused by the electrolyte.

[0010] In addition, natural graphite has a disadvantage of high electrode expansion compared to artificial graphite. In addition, the internal pores generated during spheroidization of natural graphite are larger than those of artificial graphite, and the resulting coating film causes problems of gas generation and reduced high temperature storage characteristics, the gas originating from side reactions occurring at high temperatures through such a large number of internal pores. Summary of the invention

[0011] Technical issues

[0012] The present invention is designed to solve the problems of the related art, and thus the present invention is directed to providing a spheroidized carbonaceous negative electrode active material having reduced internal pores and improved sphericity, a preparation method thereof, and a negative electrode and a lithium secondary battery comprising the same.

[0013] The present invention also provides a negative electrode including the negative electrode active material and a lithium secondary battery including the negative electrode.

[0014] Technical Solution

[0015] According to the present invention, according to the following embodiments, a spheroidized carbonaceous negative electrode active material, a preparation method thereof, and a negative electrode and a lithium secondary battery including the same are provided.

[0016] According to a first embodiment of the present invention, there is provided a method for preparing a spheroidized carbonaceous negative electrode active material, comprising the following steps:

[0017] mixing flake graphite, solid asphalt and liquid asphalt, and spheroidizing the resulting mixture to prepare spheroidized granulated particles;

[0018] calcining the spheroidized granulated particles;

[0019] Carbon coating is performed on the calcined spheroidized granulated particles;

[0020] heat treating the carbon-coated spheroidized granulated particles; and

[0021] The heat-treated product is disintegrated.

[0022] According to a second embodiment of the present invention, there is provided a method for preparing a spheroidized carbonaceous negative electrode active material as defined in the first embodiment, wherein the weight ratio of flaky graphite to the mixture of solid pitch and liquid pitch is 92:8 to 98:2.

[0023] According to a third embodiment of the present invention, there is provided a method for preparing a spheroidized carbonaceous negative electrode active material as defined in the first or second embodiment, wherein the weight ratio of the solid pitch to the liquid pitch is 50:50 to 90:10.

[0024] According to a fourth embodiment of the present invention, there is provided a spheroidized carbonaceous negative electrode active material having a ... 2 / g to 2.5m 2 / g specific surface area and 0.7e -2 cm 3 / g to 1.8e -2 cm 3 / g of total pore volume, and the pores with a size of 24 nm or more in the negative electrode active material have a pore volume of 0.2 m 2 / g to 0.6m 2 / g specific surface area.

[0025] According to a fifth embodiment of the present invention, there is provided a spheroidized carbonaceous negative electrode active material as defined in the fourth embodiment, which has a carbonaceous negative electrode active material having a molecular weight of 1.0 m 2 / g to 2.0m 2 / g specific surface area.

[0026] According to a sixth embodiment of the present invention, there is provided a spheroidized carbonaceous negative electrode active material as defined in the fourth or fifth embodiment, which has a 0.8e -2 cm 3 / g to 1.4e -2 cm 3 / g total pore volume.

[0027] According to a seventh embodiment of the present invention, there is provided a spheroidized carbonaceous negative electrode active material as defined in any one of the fourth to sixth embodiments, wherein the pores having a size of 24 nm or more in the negative electrode active material have a diameter of 0.3 m. 2 / g to 0.5m 2 / g specific surface area.

[0028] According to an eighth embodiment of the present invention, there is provided a spheroidized carbonaceous negative electrode active material as defined in any one of the fourth to seventh embodiments, which has an average particle diameter of 10 μm to 20 μm.

[0029] According to a ninth embodiment of the present invention, there is provided a carbonaceous negative electrode active material after spheroidization as defined in any one of the fourth to eighth embodiments, which has a sphericity of 0.82 to 0.98.

[0030] According to a tenth embodiment of the present invention, there is provided a negative electrode comprising a current collector and a negative electrode active material layer disposed on at least one surface of the current collector, wherein the negative electrode active material layer comprises the spheroidized carbonaceous negative electrode active material as defined in any one of the fourth to ninth embodiments.

[0031] According to an eleventh embodiment of the present invention, there is provided a lithium secondary battery including the negative electrode as defined in the tenth embodiment.

[0032] Beneficial Effects

[0033] According to one embodiment of the present invention, instead of spheroidization using only flaky graphite according to the related art, spheroidization is performed after mixing flaky graphite with solid pitch and liquid pitch. In this way, a spheroidized carbonaceous negative electrode active material with improved sphericity and reduced internal pores can be provided. When the negative electrode active material is applied to the negative electrode of a secondary battery, a secondary battery showing reduced internal stress and improved expansion characteristics and having a high capacity retention rate during high temperature storage can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The accompanying drawings show a preferred embodiment of the present invention and the aforementioned disclosure to provide a further understanding of the technical features of the present invention. Therefore, the present invention should not be construed as being limited to the accompanying drawings. On the other hand, for a clearer description, the shapes, sizes, scales or proportions of some components in the accompanying drawings may be exaggerated.

[0035] Figure 1 is a schematic diagram illustrating a spheroidizing step of a method for preparing a spheroidized carbonaceous negative electrode active material according to one embodiment of the present invention.

[0036] Figure 2 is a schematic diagram showing a spheroidization step of a method for preparing a spheroidized carbonaceous negative electrode active material according to the prior art. DETAILED DESCRIPTION

[0037] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings. Before the description, it should be understood that the terms used in this specification and the appended claims should not be interpreted as limited to the general meaning and dictionary meaning, but should be interpreted based on the meaning and concept corresponding to the technical aspects of the present invention based on the principle that the inventor is allowed to appropriately define the terms for the best interpretation.

[0038] In one aspect of the present invention, a method for preparing a spheroidized carbonaceous negative electrode active material is provided, comprising the following steps:

[0039] mixing flake graphite, solid asphalt and liquid asphalt, and spheroidizing the resulting mixture to prepare spheroidized granulated particles;

[0040] calcining the spheroidized granulated particles;

[0041] Carbon coating is performed on the calcined spheroidized granulated particles;

[0042] heat treating the carbon-coated spheroidized granulated particles; and

[0043] The heat-treated product is disintegrated.

[0044] When spheroidization is performed by using only flaky graphite according to the prior art, a large number of internal pores are generated in the spheroidized particles, and side reactions occur in such internal pores. In order to solve the above problems, according to the present invention, spheroidization is performed after mixing flaky graphite with solid pitch and liquid pitch. In this way, the present invention is directed to providing a carbonaceous negative electrode active material after spheroidization, which has reduced internal pores and improved sphericity, suppresses electrode expansion when used for an electrode of a battery, and provides improved high-temperature storage characteristics for the battery.

[0045] In the following, each step of the method will be explained in detail.

[0046] First, flaky graphite is mixed with solid pitch and liquid pitch, and the resulting mixture is spheroidized to prepare spheroidized granulated particles.

[0047] In this step, flaky graphite, solid pitch, and liquid pitch are prepared in a predetermined weight ratio, and then mixed and spheroidized to prepare spheroidized granulated particles.

[0048] In this step, while flaky graphite and solid pitch are brought into contact with each other to form granulated particles, solid pitch particles having a smaller average particle size than flaky graphite are inserted into the empty spaces (voids) formed between the flaky graphite particles, so that the empty spaces (voids) can be filled with solid pitch. In this way, the internal pores are reduced, and then the liquid pitch infiltrates and fills the reduced internal pores. As a result, the internal pores can be significantly reduced, thereby providing significantly densified spheroidized particles.

[0049] In this step, a mixture of flaky graphite, solid pitch and liquid pitch can be used as a raw material, and a spheroidization process commonly known to those skilled in the art is carried out, such as applying a mechanical treatment, including impact compression, friction or shearing force. The mechanical treatment can be carried out by using a spheroidization device commonly known to those skilled in the art, and a specific example of such a device includes a mill, such as a reverse jet mill (Hosokawa Micron, JP), an ACM pulverizer (Hosokawa Micron, JP) or a jet ejector (current jet) (Nissin, JP), a granulator, such as SARARA (Kawasaki Heavy Industries, Ltd., JP), GRANUREX (Freund Corporation, JP), New-Gra Machine (Seishin, JP) or Acromarter (Kosokawa Micron, JP), a kneader, such as a dispersion kneader or a double roller, a compression shearing processing device, such as a mechanical-micro system, an extruder, a ball mill, a planetary mill, a mechanical-melting system, Nobilta, a hybrid or rotary ball mill, etc.

[0050] According to one embodiment of the present invention, the mixture is introduced into a spheroidizing device, a mechanical shear force is applied thereto to form a granulated particle core, and then a spheroidized granulated particle having one or more surface layers can be formed, the surface layers being stacked in a concentric circle direction and spherically bonded to the surface portion of the granulated particle core. The granulated particle core and the surface layer are formed simultaneously, thereby forming a spheroidized granulated particle.

[0051] According to one embodiment of the present invention, a rotary processing machine is used to repeatedly process a mixture of flaky graphite, solid graphite and liquid asphalt to obtain granulated particles after spheroidization. As a result of repeated rotation, flaky graphite, solid asphalt and liquid asphalt are formed into granulated particles by crushing caused by collision and friction between the mixture of flaky graphite and solid asphalt and the inner surface of the processing machine, shearing caused by shear stress, etc. Finally, granulated particles after spheroidization can be obtained. Here, the crushing time and crushing rate can be controlled within an appropriate range according to the amount of graphite introduced into the machine.

[0052] In addition, this step may also include a step of isotropically pressurizing the obtained spheroidized granulated particles to improve the contact between the flaky graphite, solid asphalt and liquid asphalt contained in the spheroidized granulated particles.

[0053] Here, "isotropic pressing" means three-dimensionally uniformly pressing the spheroidized granulated particles. To isotropically pressurize the spheroidized granulated particles, water or argon gas may be used as a medium at room temperature, or cold isotropic pressing may be performed at room temperature.

[0054] In addition, although the pressure applied during the isotropic pressurization of the granulated particles after spheroidization is not particularly limited, a pressure of 50 atm to 100 atm is preferred, and a pressure of 100 atm to 200 atm is more preferred.

[0055] The term "flaky graphite" refers to natural graphite having a flaky particle shape, and can be obtained by pulverizing natural graphite having a flaky, plate-like, crushed, sheet-like, or the like shape to a desired particle size.

[0056] Solid asphalt can be the asphalt currently used. For example, solid asphalt can be obtained by crushing coal tar pitch, petroleum pitch, synthetic asphalt, wood tar pitch, etc. Liquid asphalt can be obtained by dissolving liquid resin or solid asphalt in a solvent for coating, and carbonizing the resulting product. Here, the special example of solvent includes hexane, toluene, tetrahydrofuran (THF), quinoline, N-methyl pyrrolidone (NMP), ethanol, etc.

[0057] According to one embodiment of the present invention, the flaky graphite has an average particle size of 30 μm to 100 μm or 50 μm to 80 μm. The solid pitch has an average particle size smaller than the average particle size of the flaky graphite, and the average particle size of the solid pitch may be 2 μm to 10 μm or 3 μm to 5 μm. When the average particle sizes of the flaky graphite and the solid pitch meet the above ranges, the internal pores can be reduced and the spheroidization step can be advantageously promoted.

[0058] According to one embodiment of the present invention, the weight ratio of flaky graphite to the mixture of solid asphalt and liquid asphalt can be 92: 8 to 98: 2 or 94: 6 to 96: 4. When the weight ratio of flaky graphite to the asphalt mixture (mixture of solid asphalt and liquid asphalt) satisfies the range defined above, the internal pores can be advantageously reduced.

[0059] According to one embodiment of the present invention, the weight ratio of solid asphalt to liquid asphalt may be 50:50 to 90:10, or 75:25 to 87: 13. When the weight ratio of solid asphalt to liquid asphalt satisfies the above defined range, internal pores may be advantageously reduced.

[0060] Referring to the embodiment of the present invention Figure 1 , flaky graphite 110, solid pitch 120 and liquid pitch 130 are mixed, and then the resulting mixture is subjected to the above-mentioned spheroidization process to obtain spheroidized granulated particles 100. Here, in the spheroidized granulated particles 100, the empty spaces formed in the flaky graphite particles 110 are filled with the solid pitch 120, and the liquid pitch 130 penetrates therein, so that the internal pores 130 are significantly reduced.

[0061] On the other hand, referring to the prior art Figure 2 , the flaky graphite 210 is used alone and subjected to a spheroidization process. In this case, the spheroidized granulated particles 200 can be obtained, but the empty spaces formed in the flaky graphite particles 210 remain in the spheroidized granulated particles 200 to provide a large number of internal pores 220.

[0062] Next, the spheroidized granulated particles are calcined.

[0063] In this calcining step, the spheroidized granulated particles obtained by the previous step are heated to a temperature of 800° C. to 1,800° C. or 1,000° C. to 1,400° C., so that the solid pitch and liquid pitch forming the spheroidized granulated particles can be carbonized. As a result, the flaky graphite particles in the spheroidized granulated particles are interconnected and fixed to each other, the internal pores of the spheroidized granulated particles are filled, and the solid pitch and liquid pitch coated on the surface of the flaky graphite particles are converted into amorphous carbon. In this way, the spheroidized granulated particles can be settled more densely.

[0064] Then, the calcined spheroidized granulated particles are coated with carbon.

[0065] In the carbon coating step, the spheroidized granulated particles baked by the previous step are uniformly mixed with the carbon coating material so that the carbon coating material can be attached to the surface of the baked spheroidized granulated particles, and then the resulting product is carbonized to form a carbon coating on the surface of the baked spheroidized granulated particles. The carbon material forms a coating on the surface of the baked spheroidized granulated particles so that the flaky graphite, solid asphalt and liquid asphalt forming the spheroidized granulated particles can be further combined with each other. In this way, the stability of the spheroidized granulated particles can be prevented from being reduced during repeated charge / discharge cycles.

[0066] The carbon coating material can be prepared from a carbon precursor, which contains sucrose, phenolic resin, naphthalene resin, polyvinyl alcohol resin, furfuryl alcohol resin, polyacrylonitrile resin, polyamide resin, furan resin, cellulose resin, styrene resin, polyimide resin, epoxy resin or vinyl chloride resin, coal tar, petroleum asphalt, polyvinyl chloride, mesophase pitch, tar, block copolymer, low molecular weight heavy oil or a mixture thereof.

[0067] Here, the amount of the carbon coating material may be 1 to 10 parts by weight or 3 to 6 parts by weight based on 100 parts by weight of the calcined spheroidized granulated particles. When the amount of the carbon coating satisfies the above-defined range, the problem of decreased capacity per unit weight caused by forming an overly thick coating and decreased initial efficiency caused by irreversibility, or the problem of increased side reactions caused by increased specific surface area of ​​the active material caused by forming an overly thin coating, and the problem of decreased life efficiency caused by peeling of the coating during charge / discharge cycles can be prevented. It can also help to form an initial SEI layer, and thus improve the stability of the spheroidized granulated particles during repeated charge / discharge cycles.

[0068] The method for mixing the surface of the calcined spheroidized granulated particles with the carbon coating material is not particularly limited, and any method commonly known to those skilled in the art can be used. For example, the mixing can be carried out by using mechanical and chemical processes such as using a kneader, such as a twin roll, blade, mechanical micro system, extruder, ball mill, planetary mill, mechanical-melt system, Nobilta, hybrid or rotary ball mill, or by using a spray drying process or an emulsification process.

[0069] After the carbon coating material is uniformly mixed with the calcined spheroidized granulated particles as described above, the resulting mixture is carbonized at a temperature of 900° C. to 1,300° C. for 12 to 48 hours, so that a carbon coating can be formed on the calcined spheroidized granulated particles. The formed carbon coating may contain amorphous carbon or crystalline carbon. When the carbonization conditions are met, the carbon coating material can be fully stabilized, impurities in the carbon coating material can be completely removed, and the coating surface properties of the carbon coating material can be prevented from being reduced at high temperatures.

[0070] Then, the carbon-coated spheroidized granulated particles are heat treated.

[0071] In this heat treatment step, the carbon coating formed on the surface of the spheroidized granulated particles by the carbonization in the previous step can have improved surface properties, and the graphite material forming the spheroidized granulated particles can have improved crystallinity and homogeneity.

[0072] According to one embodiment of the present invention, the carbon-coated spheroidized granulated particles obtained from the above steps may be heat-treated at a temperature of 1,100 to 1,600° C. or 1,200 to 1,400° C. for 3 to 24 hours or 6 to 12 hours. Then, the heat-treated product is disintegrated.

[0073] The spheroidized granulated particles obtained from the carbonization in the carbon coating step of the spheroidized granulated particles and the heat treatment step of the carbon-coated spheroidized granulated particles may be agglomerated with each other. Therefore, the agglomerated particles are subjected to a disintegration process.

[0074] In the disintegration step, the agglomerated particles can be easily disintegrated by simply applying a slight shear force to the agglomerated spheroidized granulated particles. The disintegration process is not particularly limited. For example, the disintegration can be performed by using a stirrer with a stirring blade, or by using a known mill such as a jet mill, a vibration mill, a pin mill, a hammer mill, etc.

[0075] In another aspect of the present invention, a spheroidized carbonaceous negative electrode active material is provided, which has a 1.0 m 2 / g to 2.5m 2 / g specific surface area and 0.7e -2 cm 3 / g to 1.8e -2 cm 3 / g of total pore volume, and the pores with a size of 24 nm or more in the negative electrode active material have a pore volume of 0.2 m 2 / g to 0.6m 2 / g specific surface area.

[0076] According to one embodiment of the present invention, the spheroidized carbonaceous negative electrode active material can be obtained by the above method for preparing the spheroidized carbonaceous negative electrode active material.

[0077] The negative electrode active material has a 1.0 m 2 / g to 2.5m 2 According to one embodiment of the present invention, the negative electrode active material may have a specific surface area of ​​1.0 m 2 / g to 2.0m 2 / g or 1.5m 2 / g to 1.7m 2 When the specific surface area of ​​the negative electrode active material satisfies the above-defined range, side reactions with the electrolyte may be reduced, thereby advantageously providing improved high-temperature storage characteristics.

[0078] Here, the specific surface area is measured by the BET method. Specifically, the specific surface area can be calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77K) using BELSOR-minoII obtained from BEL, Japan.

[0079] The negative electrode active material has 0.7e -2 cm 3 / g to 1.8e -2 cm 3 According to one embodiment of the present invention, the negative electrode active material may have a total pore volume of 0.8e -2 cm 3 / g to 1.4e -2 cm 3 / g or 1.09e -2 cm 3 / g to 1.25e -2 cm 3 When the total pore volume of the negative electrode active material satisfies the above-defined range, side reactions with the electrolyte may be reduced, thereby advantageously providing improved high-temperature storage characteristics.

[0080] Here, the total pore volume of the negative electrode active material can be measured similarly to the measurement of the specific surface area by the BET method and by using the same system as that for the measurement of the specific surface area.

[0081] In addition, the pores with a size of 24 nm or more in the negative electrode active material have a size of 0.2 m 2 / g to 0.6m 2 According to one embodiment of the present invention, the specific surface area may be 0.3 m 2 / g to 0.5m 2 / g or 0.39m 2 / g to 0.44m 2 When the specific surface area of ​​pores having a size of 24 nm or more in the negative electrode active material satisfies the above-defined range, side reactions with the electrolyte can be advantageously reduced.

[0082] The specific surface area of ​​pores having a size of 24 nm or more in the negative electrode active material is determined similarly to the determination of the specific surface area by the BET method and by using the same system as that for the determination of the specific surface area.

[0083] In particular, it is important to satisfy all of the following conditions: the negative electrode active material has 1.0 m 2 / g to 2.5m 2 / g specific surface area; the negative electrode active material has 0.7e -2 cm 3 / g to 1.8e -2 cm 3 / g of total pore volume; and the pores with a size of 24nm or more in the negative electrode active material have a 0.2m 2 / g to 0.6m 2 / g of specific surface area, as this reduces irreversibility, suppresses side reactions, and suppresses expansion caused by gas generation during long-term storage.

[0084] According to one embodiment of the present invention, the carbonaceous negative electrode active material after spheroidization may have an average particle size of 10 μm to 20 μm or 11 μm to 18 μm.

[0085] Average particle size D 50 It means the particle size at the 50% point in the cumulative distribution of particle number as a function of particle size. For example, D 90 means the particle size at the 90% point in the cumulative distribution of the number of particles as a function of particle size, and D 10 It means the particle size at the 10% point in the cumulative distribution of particle number as a function of particle size.

[0086] The average particle size can be determined by using a laser diffraction method. Specifically, the powder to be analyzed is dispersed in a dispersion medium and introduced into a commercially available laser diffraction particle size analyzer (e.g., Microtrac S3500) to measure the difference in the diffraction pattern depending on the particle size when the particles pass through the laser beam, and then the particle size distribution can be calculated. Then, D can be determined by calculating the particle size at the 10%, 50%, and 90% points in the cumulative distribution of the number of particles depending on the particle size in the analyzer system, respectively. 10 , D 50 and D 90 .

[0087] The carbonaceous negative electrode active material after spheroidization may have a sphericity of 0.82 to 0.98 or 0.88 to 0.92.

[0088] The sphericity may be a value obtained by dividing the circumference of a circle having the same area as the projected image of the negative electrode active material by the circumference of the projected image, and specifically, may be represented by the following Mathematical Formula 1. The sphericity may be measured by using a particle shape analyzer such as Sysmex FPIA3000 available from Malvern Co.

[0089] [Mathematical formula 1]

[0090] Sphericity = circumference of a circle having the same area as the projected image of the active material / circumference of the projected image

[0091] According to another aspect of the present invention, a negative electrode including a negative electrode active material is provided.

[0092] Specifically, a negative electrode according to one embodiment of the present invention includes a current collector and a negative electrode active material layer provided on at least one face of the current collector and including the negative electrode active material according to one embodiment of the present invention.

[0093] The electrode layer may be formed by coating a slurry for a negative electrode active material layer prepared by dispersing the negative electrode active material according to the present invention, a binder and a conductive material in a solvent on at least one surface of a current collector, followed by drying and rolling.

[0094] The current collector is not particularly limited as long as it has conductivity without causing any chemical changes in the corresponding battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. Although the current collector is not particularly limited in terms of its thickness, it can have a thickness of 3 μm to 500 μm.

[0095] The negative electrode active material may be used in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode slurry composition.

[0096] The binder is a component that helps to bind between the conductive material and the active material or to the current collector, and is generally used in an amount of 0.1 wt % to 20 wt % based on the total weight of the negative electrode slurry composition. Specific examples of binders include polyvinylidene fluoride-co-hexafluoropropylene (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylate, styrene-butadiene rubber (SBR), lithium polyacrylate (Li-PAA), etc. More particularly, when lithium polyacrylate is used for a negative electrode containing an active material with a high silicon content of about 80%, it can impart higher adhesion compared to other binders such as SBS / CMC. Due to the above characteristics, the advantage of lithium polyacrylate is that when lithium polyacrylate is used for Si-based negative electrodes, a high capacity retention rate can be achieved during charge / discharge.

[0097] The conductive material is not particularly limited as long as it does not cause chemical changes in the corresponding battery and has conductivity. Specific examples of the conductive material include: carbon black, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black or thermal black; conductive fibers, such as carbon fibers or metal fibers; fluorinated carbon; metal powders, such as aluminum or nickel powder; conductive whiskers, such as zinc oxide or potassium titanate; conductive metal oxides, such as titanium oxide; conductive materials, such as polyphenylene derivatives, etc. Based on the total weight of the negative electrode slurry composition, the conductive material can be added in an amount of 0.1 wt% to 20 wt%.

[0098] The dispersion medium may include water or an organic solvent such as N-methyl-2-pyrrolidone (NMP), and may be used in an amount such that the negative electrode slurry including the negative electrode active material and optionally a binder and a conductive material may have a desired viscosity level.

[0099] In addition, the coating process of the negative electrode slurry is not particularly limited as long as it is a method currently used in the art. For example, a coating process using a slot die can be used. In addition, a Meyer rod coating process, a gravure coating process, a dip coating process, a spray coating process, etc. can be used.

[0100] According to another aspect of the present invention, a lithium secondary battery including a negative electrode is provided. In particular, the lithium secondary battery can be obtained by injecting an electrolyte containing a lithium salt into an electrode assembly, wherein the electrode assembly includes a positive electrode, the negative electrode described above, and a separator interposed between the positive electrode and the negative electrode.

[0101] The positive electrode can be obtained by mixing a positive electrode active material, a conductive material, a binder and a solvent to form a slurry and directly coating the slurry on a metal current collector, or casting the slurry on a separate support, peeling the positive electrode active material film from the support and laminating the film on a metal current collector.

[0102] The positive electrode active material used in the positive electrode active material layer may be any one of the active material particles selected from the group consisting of LiCoO2, LiNiO2, LiMn2O4, LiCoPO4, LiFePO4 and LiNi 1-x-y-z Co x M1 y M2 z O2 (wherein M1 and M2 each independently represent any one selected from Al, Ni, Co, Fe, Mn, V, Cr, Ti, W, Ta, Mg and Mo, x, y and z each independently represent the atomic ratio of the elements forming the oxide, and 0≤x<0.5, 0≤y<0.5, 0≤z<0.5, and 0<x+y+z≤1) or a mixture of at least two thereof.

[0103] On the other hand, the same conductive material, binder, and solvent as those used to produce the negative electrode may be used.

[0104] The separator can be a conventional porous polymer film conventionally used as a separator. For example, the porous polymer film can be a porous polymer film made of polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene-butene copolymers, ethylene / hexene copolymers or ethylene / methacrylate copolymers. This porous polymer film can be used alone or in the form of a laminate. In addition, an insulating film with high ion permeability and mechanical strength can be used. The separator can include a safety enhanced separator (SRS), which includes a ceramic material coated on the surface of the separator with a small thickness. In addition, conventional porous nonwoven fabrics can be used, such as nonwoven fabrics made of high melting point glass fibers or polyethylene terephthalate fibers, but the scope of the present invention is not limited thereto.

[0105] The electrolyte contains a lithium salt as an electrolyte salt and an organic solvent for dissolving the lithium salt.

[0106] Any lithium salt conventionally used in electrolytes for secondary batteries may be used without particular limitation. For example, the anion of the lithium salt may be any one selected from the following: - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .

[0107] The organic solvent contained in the electrolyte may be any organic solvent conventionally used without particular limitation. Typical examples of the organic solvent include at least one selected from the group consisting of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methylpropyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, cyclopentane, γ-butyrolactone, propylene sulfite, and tetrahydrofuran.

[0108] Especially, in carbonate organic solvent, ethylene carbonate and propylene carbonate as cyclic carbonate are organic solvents with high viscosity and high dielectric constant, and because they can easily dissociate the lithium salt in the electrolyte, therefore can preferably use.When such cyclic carbonate is mixed with the straight-chain carbonate (for example dimethyl carbonate or diethyl carbonate) with low viscosity and low dielectric constant and used, can more preferably prepare the electrolyte with higher conductivity.

[0109] Optionally, the electrolyte used according to the present invention may further contain additives contained in conventional electrolytes such as an overcharge preventer and the like.

[0110] The lithium secondary battery according to one embodiment of the present invention can be obtained by inserting a separator between a positive electrode and a negative electrode to form an electrode assembly, introducing the electrode assembly into a pouch battery case, a cylindrical battery case or a prismatic battery case, and then injecting an electrolyte therein. In one variant, the lithium secondary battery can be obtained by stacking the electrode assemblies, impregnating the stack with an electrolyte, and introducing the resulting product into a battery case, which is then sealed.

[0111] According to one embodiment of the present invention, the lithium secondary battery may be a stacked type battery, a wound type battery, a stacked and folded type battery, or a cable type battery.

[0112] The lithium secondary battery according to the present invention can be used in a battery cell used as a power source for a small device, and can preferably be used as a unit cell of a medium or large battery module containing a plurality of battery cells. Specific examples of such medium or large devices include electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In particular, lithium secondary batteries can be used for batteries for hybrid electric vehicles requiring high output and new and renewable energy storage batteries.

[0113] Embodiments will be described more fully hereinafter so that the present invention can be easily understood. However, the following examples can be embodied in many different forms and should not be construed as being limited to the exemplary embodiments set forth herein. On the contrary, these exemplary embodiments are provided so that the present invention will be in-depth and comprehensive, and the scope of the present invention will be fully communicated to those skilled in the art.

[0114] Example 1

[0115] (Preparation of carbonaceous negative electrode active material after spheroidization)

[0116] Flake graphite with an average particle size of 70 μm, solid pitch and liquid pitch with an average particle size of 5 μm were prepared at a weight ratio of 95:4:1, mixed by using a ball mill, and spheroidized by using a reverse jet mill (Hosokawa Micron, JP) to obtain spheroidized granulated particles. Then, 100 parts by weight of the obtained spheroidized granulated particles were mixed with 5 parts by weight of solid pitch as a carbon coating material, and the obtained mixture was carbonized by using a ball mill at a temperature of 1,150°C for 24 hours to obtain carbon-coated spheroidized granulated particles.

[0117] Then, the carbon-coated spheroidized granulated particles were heat-treated at a temperature of 1,350° C. for 12 hours.

[0118] Then, the heat-treated product is disintegrated to obtain a spheroidized carbonaceous negative electrode active material.

[0119] (Manufacturing of negative electrode)

[0120] The spheroidized carbonaceous negative electrode active material obtained as described above, Super C65 as a conductive material, styrene butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 96.6:1:1.3:1.1, and water was added thereto to prepare a negative electrode slurry. The resulting slurry was coated on a copper foil and vacuum dried at a temperature of about 130°C for 10 hours to obtain a negative electrode slurry with an area of ​​1.4875 cm 2 Here, the negative electrode with a loading capacity of 3.61 mAh / cm 2 of the negative electrode.

[0121] (Manufacturing of coin-type secondary battery)

[0122] The negative electrode obtained as described above was used as a working electrode, and a 2 Li metal is used as a counter electrode. In addition, a porous polyethylene separator is inserted between the working electrode and the counter electrode to form an electrode assembly. Then, ethylene carbonate (EC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:4, and 0.5 wt % of vinyl carbonate (VC) and 1M LiPF6 as additives for non-aqueous electrolytes are added to the mixed solvent to prepare a non-aqueous electrolyte. The electrode assembly is housed in a coin-type housing, and a non-aqueous electrolyte is injected therein to obtain a coin-type half-cell secondary battery.

[0123] Example 2

[0124] A spheroidized carbonaceous negative electrode active material was obtained in the same manner as in Example 1, except that flaky graphite, solid pitch, and liquid pitch were prepared at a weight ratio of 96:3:1.

[0125] In addition, a secondary battery was obtained in the same manner as in Example 1, except that the negative electrode active material obtained as described above was used.

[0126] Example 3

[0127] A spheroidized carbonaceous negative electrode active material was obtained in the same manner as in Example 1, except that flaky graphite, solid pitch, and liquid pitch were prepared at a weight ratio of 94:5:1.

[0128] In addition, a secondary battery was obtained in the same manner as in Example 1, except that the negative electrode active material obtained as described above was used.

[0129] Example 4

[0130] A spheroidized carbonaceous negative electrode active material was obtained in the same manner as in Example 1, except that flaky graphite, solid pitch, and liquid pitch were prepared at a weight ratio of 95:3:2.

[0131] In addition, a secondary battery was obtained in the same manner as in Example 1, except that the negative electrode active material obtained as described above was used.

[0132] Comparative Example 1

[0133] A spheroidized carbonaceous negative electrode active material was obtained in the same manner as in Example 1, except that flaky graphite alone was used instead of solid pitch and liquid pitch.

[0134] In addition, a secondary battery was obtained in the same manner as in Example 1, except that the negative electrode active material obtained as described above was used.

[0135] Comparative Example 2

[0136] A spheroidized carbonaceous negative electrode active material was obtained in the same manner as in Example 1, except that flaky graphite and solid pitch were prepared at a weight ratio of 96:4, and liquid pitch was not used.

[0137] In addition, a secondary battery was obtained in the same manner as in Example 1, except that the negative electrode active material obtained as described above was used.

[0138] Comparative Example 3

[0139] A spheroidized carbonaceous negative electrode active material was obtained in the same manner as in Example 1, except that flaky graphite and solid pitch were prepared at a weight ratio of 95:5 without using liquid pitch.

[0140] In addition, a secondary battery was obtained in the same manner as in Example 1, except that the negative electrode active material obtained as described above was used.

[0141] Experimental methods and results

[0142] The specific surface area of ​​the negative electrode active material, the total pore volume of the negative electrode active material, and the size of the pores in the negative electrode active material are Surface area of ​​pores larger than 24 nm

[0143] By using the BET method, the specific surface area, total pore volume, and specific surface area of ​​pores with a size of 24 nm or more in each of the negative electrode active materials according to Examples 1 to 3 and Comparative Examples 1 to 3 were measured. In particular, the specific surface area, total pore volume, and specific surface area of ​​pores with a size of 24 nm or more were calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77K) using BELSOR-mino II available from BEL, Japan.

[0144] Average particle size of negative electrode active material

[0145] The negative electrode active materials according to Examples 1 to 3 and Comparative Examples 1 to 3 were each dispersed in water as a dispersion medium and then introduced into a laser diffraction particle size analyzer (Microtrac S3500) to measure the difference in diffraction patterns depending on the particle size when the negative electrode active material particles passed through a laser beam and then calculate the particle size distribution. 50 That is, the average particle size is determined by calculating the particle size at the 50% point in the cumulative distribution of the particle numbers according to the particle sizes in the analyzer system.

[0146] Sphericity of negative electrode active materials

[0147] The sphericity of each of the negative active materials according to Examples 1 to 3 and Comparative Examples 1 to 3 is defined by the following Mathematical Formula 1. The sphericity was measured by using a Sysmex FPIA3000 particle shape analyzer available from Malvern Corporation.

[0148] [Mathematical formula 1]

[0149] Sphericity = circumference of a circle having the same area as the projected image of the active material / circumference of the projected image

[0150] Expansion characteristics

[0151] The expansion ratio of each secondary battery according to Examples 1 to 3 and Comparative Examples 1 to 3 was measured after 30 charge / discharge cycles under the conditions of a charge / discharge current of 0.1 C and a charge / discharge voltage of 5 mV to 1.5 V. The results are shown in Table 1 below.

[0152] Here, the expansion ratio (%) is defined by the following formula:

[0153] Expansion ratio (%) = [(electrode thickness after charge / discharge cycle - initial electrode thickness) / (initial electrode thickness)] × 100

[0154] High temperature storage characteristics

[0155] After each of the secondary batteries according to Examples 1 to 3 and Comparative Examples 1 to 3 was stored at 60° C. at 100% SOC (state of charge) for 4 weeks, it was charged / discharged at room temperature under the conditions of a charge / discharge current of 0.1 C and a charge / discharge voltage of 5 mV to 1.5 V to determine the capacity retention rate. The results are shown in Table 1 below.

[0156] Here, the capacity retention rate (%) is defined by the following formula:

[0157] Capacity retention rate (%) = [(capacity after high temperature storage) / (initial capacity)] × 100

[0158] [Table 1]

[0159]

[0160] As can be seen from Table 1, each of the secondary batteries using the negative electrode active materials according to Examples 1 to 3 showed improved results of expansion characteristics and high temperature storage capacity retention characteristics compared to the secondary batteries using the negative electrode active materials according to Comparative Examples 1 to 3.

Claims

1. A method for preparing a spheroidized carbonaceous negative electrode active material, the method comprising the following steps: Mixing flaky graphite, solid asphalt and liquid asphalt, and spheroidizing the resulting mixture to prepare spheroidized granulated particles, wherein the weight ratio of the flaky graphite to the mixture of the solid asphalt and the liquid asphalt is 92:8 to 98:2; calcining and carbon coating the spheroidized granulated particles to form carbon-coated spheroidized granulated particles, wherein the calcining is performed by heating the spheroidized granulated particles to a temperature of 800 to 1800° C.; heat treating the carbon-coated spheroidized granulated particles at a temperature of 1100 to 1600° C. for 3 to 24 hours; and The heat-treated product is disintegrated. 2 . The method for preparing a spheroidized carbonaceous negative electrode active material according to claim 1 , wherein the weight ratio of the solid pitch to the liquid pitch is 50:50 to 90:

10.

3. A spheroidized carbonaceous negative electrode active material having a 1.0 m 2 / g to 2.0m 2 / g specific surface area and 0.7e -2 cm 3 / g to 1.8e -2 cm 3 Total pore volume / g, In the negative electrode active material, the pores with a size of 24 nm or more have a size of 0.2 m 2 / g to 0.6m 2 / g specific surface area, The preparation of the spheroidized carbonaceous negative electrode active material comprises the following steps: While flaky graphite and solid asphalt are brought into contact with each other to form granulated particles, solid asphalt particles having a smaller average particle size than that of the flaky graphite are inserted into the empty spaces formed between the flaky graphite particles, so that the empty spaces can be filled with solid asphalt, thereby reducing the internal pores, and then liquid asphalt penetrates and fills the reduced internal pores.

4. The spheroidized carbonaceous negative electrode active material according to claim 3 has a 0.8e -2 cm 3 / g to 1.4e -2 cm 3 / g total pore volume.

5. The spheroidized carbonaceous negative electrode active material according to claim 3, wherein in the negative electrode active material, the pores with a size of 24 nm or more have a size of 0.3 m 2 / g to 0.5m 2 / g specific surface area.

6. The spheroidized carbonaceous negative electrode active material according to claim 3, having an average particle size of 10 μm to 20 μm, The average particle size is D 50 It means the particle size at the 50% point in the cumulative distribution of the number of particles as a function of the particle size, and is determined by using a laser diffraction method.

7. The spheroidized carbonaceous negative electrode active material according to claim 3, having a sphericity of 0.82 to 0.98, wherein the sphericity is a value obtained by dividing the circumference of a circle having the same area as the projected image of the negative electrode active material by the circumference of the projected image.

8. A negative electrode comprising a current collector and a negative electrode active material layer disposed on at least one surface of the current collector, The negative electrode active material layer comprises the spheroidized carbonaceous negative electrode active material according to any one of claims 3 to 7. 9 . A lithium secondary battery comprising the negative electrode according to claim 8 .

Citation Information

Patent Citations

  • System for controlling electric motion gun

    KR1020190123398A

  • Composite active material for lithium secondary cell and method for manufacturing same

    WO2016125819A1